System Design of Intelligent Garbage Bin - Pan, Songzhe; Zheng, Xinyao; Chen, Yongyi; Cai, Qiaori (Scientific Journal of Technology, 2025)
In recent years, the rapid increase in the volume of waste has posed significant challenges to the environment. This project focuses on leveraging advanced technologies to address the issue of waste classification and aims to improve resource recovery efficiency and enhance environmental protection. The intelligent garbage bin, based on programmable controller technology, integrates high-precision sensing technology with deep learning algorithms. This innovation enables the garbage bin to automatically identify waste and classify it accurately, significantly improving classification efficiency and accuracy. Additionally, the intelligent garbage bin is equipped with intelligent reminder functions and a user interaction interface, which effectively enhances the public's awareness of waste classification and encourages their active participation, breaking through the limitations of traditional waste classification methods.